2022
DOI: 10.1039/d2an00540a
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenerated chemiluminescence of luminol at a boron-doped diamond electrode for the detection of hypochlorite

Abstract: Electrogenerated chemiluminescence (ECL) of luminol using boron-doped diamond electrode has been developed for hypochlorite determination. The presence of H2O2 induces the ECL signals of luminol. On the contrary, the presence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…2+ can be replaced with luminol, a classical compound for hydrogen peroxide detection in chemiluminescence, 67 and electrochemiluminescence. 23,[67][68][69][70] The classical ECL of luminol and hydrogen peroxide by using BDD was reported previously, for example, our group investigated a particular application for the detection of hypochlorite, 71 in addition to investigations of reaction mechanisms. [72][73][74] ECL from the luminol/carbonate system can be obtained through an oxidation step only (Fig.…”
Section: Hydrogen Peroxide Co-reactant From Carbonate Oxidationmentioning
confidence: 99%
“…2+ can be replaced with luminol, a classical compound for hydrogen peroxide detection in chemiluminescence, 67 and electrochemiluminescence. 23,[67][68][69][70] The classical ECL of luminol and hydrogen peroxide by using BDD was reported previously, for example, our group investigated a particular application for the detection of hypochlorite, 71 in addition to investigations of reaction mechanisms. [72][73][74] ECL from the luminol/carbonate system can be obtained through an oxidation step only (Fig.…”
Section: Hydrogen Peroxide Co-reactant From Carbonate Oxidationmentioning
confidence: 99%
“…The content of residual hypochlorite in tap water should be stringently controlled. 55,56 The pK a value of HClO is 7.49 (25 1C), and about 24.4% of HClO is ionized to ClO À in water samples of pH = 7.0. At the acidic determination medium of pH = 4.0, most of ClO À is protonated to HClO.…”
Section: Application In the Determination Of Hclo/clo à In Water Samplesmentioning
confidence: 99%
“…In short, these methods have shortcomings, for instance, timeconsuming, complex detection methods, harsh conditions, and the inability to detect ClO − in biological systems, which limits the real-time and efficient detection of ClO − . 12,13 Compared with the traditional methods of detection, fluorescent probe technology has garnered much notice due to its remarkable features, including high sensitivity, high stability, selectivity, fast response, and simple operation. 14−16 For instance, Zhu et al designed a fluorescence sensing platform for detecting glutathione (GSH).…”
Section: Introductionmentioning
confidence: 99%
“…Both chemiluminescence and chromatography are susceptible to interference from the external environment, and the instruments are unstable, so they cannot accurately detect ClO – . In short, these methods have shortcomings, for instance, time-consuming, complex detection methods, harsh conditions, and the inability to detect ClO – in biological systems, which limits the real-time and efficient detection of ClO – . , Compared with the traditional methods of detection, fluorescent probe technology has garnered much notice due to its remarkable features, including high sensitivity, high stability, selectivity, fast response, and simple operation. For instance, Zhu et al designed a fluorescence sensing platform for detecting glutathione (GSH) . Han et al reported a fluorescence analysis method for sensitive detection of H 2 O 2 , glucose, and cholesterol .…”
Section: Introductionmentioning
confidence: 99%